2007
DOI: 10.1016/j.jacc.2007.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Hyperkalemia in Patients With Heart Failure

Abstract: The risk of hyperkalemia is increased in symptomatic heart failure patients with advanced age, male gender, baseline hyperkalemia, renal failure, diabetes, or combined RAAS blockade. Although these groups derive incremental clinical benefit from candesartan, careful surveillance of serum potassium and creatinine is particularly important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(86 citation statements)
references
References 18 publications
13
70
2
1
Order By: Relevance
“…In some clinical studies of hyperkalemic events, the causal role of ␤-blockers has been assumed without the presence of a referent group (2,48), and in other studies their role has been examined only in high-risk patient populations (49 -51). Conversely, in more rigorously conducted clinical studies, ␤-blockers were not associated with hyperkalemia (6,52,53). Our study does not refute the physiologic effects of ␤-blockers, but does suggest their contribution to hyperkalemia in ambulatory patients may be relatively minor.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In some clinical studies of hyperkalemic events, the causal role of ␤-blockers has been assumed without the presence of a referent group (2,48), and in other studies their role has been examined only in high-risk patient populations (49 -51). Conversely, in more rigorously conducted clinical studies, ␤-blockers were not associated with hyperkalemia (6,52,53). Our study does not refute the physiologic effects of ␤-blockers, but does suggest their contribution to hyperkalemia in ambulatory patients may be relatively minor.…”
Section: Discussioncontrasting
confidence: 80%
“…We adjusted for characteristics that may have predisposed to hyperkalemia in the multivariable model using all available data in the 3 years preceding the index date, including the Charlson comorbidity score (0, 1, Ն2) (38;39), the number of distinct prescriptions in the preceding year (Յ5, 6 to 10, 11 to 15, 16 to 20, 21 to 25, Ն26) (40), socioeconomic status (quintiles 1 to 2, quintiles 3 to 5), congestive heart failure, coronary artery disease, and previous episodes of hyperkalemia. We adjusted for medications used within the 120-day interval before the index date that may have influenced serum potassium concentrations: Nonpotassium-sparing diuretics, potassium-sparing diuretics (7,8), potassium supplements, nonsteroidal anti-inflammatory drugs, angiotensin converting enzyme inhibitors (9), and angiotensin receptor blockers (6). We assessed for a statistical interaction by comparing the OR from the two cohorts using the technique of Altman and Bland, the OR from the first cohort reflected the risk of hyperkalemia among users of both ␤-blockers and TMP-SMX, and the OR from the second cohort reflected the same risk among users of TMP-SMX alone (41).…”
Section: Methodsmentioning
confidence: 99%
“…Rates of serum potassium Ն6.0 mmol/L were also higher with candesartan than with placebo (Table 2). Moreover, in a post hoc analysis of data from the CHARM program, single-site RAAS inhibition with candesartan was associated with a higher incidence of "clinically important" hyperkalemia (fatal hyperkalemia, or hyperkalemia requiring dose reduction, study discontinuation, or hospitalization) than was placebo (4.0% versus 1.5%; odds ratio: 2.7; 95% confidence interval (95% CI): 1.5 to 5.0) (24).…”
Section: Hyperkalemia Risk With Raas Inhibitor Monotherapymentioning
confidence: 99%
“…Moreover, a post hoc analysis of the CHARM program data showed that adding candesartan to ACEI therapy increased the combined incidence of fatal hyperkalemia and hyperkalemia requiring dose reduction, study discontinuation, or hospitalization from 2.9% to 8.4% (P Ͻ 0.0001) (24). Importantly, however, the addition of candesartan to ACEI therapy reduced cardiovascular death and HF hospitalizations in the subgroups of patients at high risk of hyperkalemia, such as those with CKD (serum creatinine Ͼ2.0 mg/dl) (24).…”
Section: Hyperkalemia Risk With Dual Raas Inhibitionmentioning
confidence: 99%
“…The paucity of existing data on long term mortality in hyperkalemia precludes the accurate future assessment of mortality benefits of these new drugs. Most published literature focuses on the effects of hyperkalemia on short-term mortality [1,7]. There is a paucity of published literature on the outcomes of hyperkalemia in survivors from the index episode.…”
Section: Archives Of Medicine Issn 1989-5216mentioning
confidence: 99%